A Reference Section Through Fast‐Spread Lower Oceanic Crust, Wadi Gideah, Samail Ophiolite (Sultanate of Oman): Petrography and Petrology. Issue 1 (3rd January 2022) - Koepke, J.; Garbe‐Schönberg, D.; Müller, T.; Mock, D.; Müller, S.; Nasir, S.
Abstract: In the absence of a complete profile through fast‐spreading modern oceanic crust, we established a reference profile through the whole paleo crust of the Samail ophiolite (Sultanate of Oman), which is regarded as the best analogue for fast‐spreading oceanic crust on land. To establish a coherent data set, we sampled the Wadi Gideah in the Wadi‐Tayin massif from the mantle section up to the sheeted dikes and performed different analytical and structural investigations on the same suite of samples. This paper reports our studies of the lower crust, a 5 km thick pile of gabbros, focusing on petrographic features and on the results of mineral analyses. Depth profiles of mineral compositions combined with petrological modeling reveal insights into the mode of magmatic formation of fast‐spreading lower oceanic crust, implying a hybrid accretion mechanism. The lower two thirds of the crust, mainly consisting of layered gabbros, formed via the injection of melt sills and in situ crystallization. Here, upward moving fractionated melts mixed with more primitive melts through melt replenishments, resulting in a slight but distinct upward differentiation trend. The upper third of the gabbroic crust is significantly more differentiated, in accord with a model of downward differentiation of a primitive parental melt originated from the axial melt lens located at the top of the gabbroic crust. Our hybrid model for crustal accretion requires a system to cool the deep crust, which was established by hydrothermal fault zones, initially formed on‐axis at very high temperatures. Plain Language Summary: In this study we investigated the Samail ophiolite in the Sultanate Oman, which is best suited to deepen our understanding how the crust under oceans forms. This is possible, since "ophiolites" represents pieces of ancient oceanic crust and shallow mantle, injected into mountain chains long time ago, when former oceans were closed by tectonic forces. In the Wadi Gideah north of the town Ibra, we sampled a continuous profile through the lower crust consisting of gabbro, with the aim to understand the formation of the lower crust, which is up to now not well understood. The results of the analysis of the minerals in the gabbros and the careful study of the petrographic features observed in the gabbros, provide deep insights into the mechanism of the magmatic emplacement of the lower crust, implying a hybrid accretion mechanism. While the lower two thirds were formed by sill intrusions and in situ crystallization, the upper third of the gabbroic crust is dominated by downward differentiation of a primitive parental melt originated from the axial melt lens located at the top of the gabbroic crust. Key Points: A reference profile through fast‐spreading lower oceanic crust was established by outcrop sampling in the Wadi Gideah (Oman ophiolite) The results imply a hybrid accretion, with in situ crystallization in the lower and subsiding crystal mushes in the upper gabbroic crust Cooling of the deep crust was established by hydrothermal fault zones initially formed at very high temperatures in the magmatic regime